2007
DOI: 10.1073/pnas.0706604104
|View full text |Cite
|
Sign up to set email alerts
|

A recurrent inversion on the eutherian X chromosome

Abstract: Chromosomal inversions have an important role in evolution, and an increasing number of inversion polymorphisms are being identified in the human population. The evolutionary history of these inversions and the mechanisms by which they arise are therefore of significant interest. Previously, a polymorphic inversion on human chromosome Xq28 that includes the FLNA and EMD loci was discovered and hypothesized to have been the result of nonallelic homologous recombination (NAHR) between near-identical inverted dup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 57 publications
6
48
0
Order By: Relevance
“…For polymorphic inversions found in natural populations, the recurrence of inversions mediated by NAHR between SDs had already been postulated by comparison of different lineages in mammals [59] or primates [21], [67], and there was some evidence that it could occur in humans as well [12], [68]. In addition, experimentally it was suggested that some inversions could appear repeatedly in human cells [69], [70], although these results should be confirmed with independent techniques.…”
Section: Discussionmentioning
confidence: 97%
“…For polymorphic inversions found in natural populations, the recurrence of inversions mediated by NAHR between SDs had already been postulated by comparison of different lineages in mammals [59] or primates [21], [67], and there was some evidence that it could occur in humans as well [12], [68]. In addition, experimentally it was suggested that some inversions could appear repeatedly in human cells [69], [70], although these results should be confirmed with independent techniques.…”
Section: Discussionmentioning
confidence: 97%
“…Given the high dynamism of these regions, it is common to find recurrent events at nearly identical locations within the genome. A 150 Kb human polymorphic inversion on chromosome Xq28, for example, has been shown to be recurrently inverted in eutherian evolution at least a dozen times [84] owing, in part, to the presence of a diverse array of duplicated sequences located at the inversion breakpoint in almost every mammalian species. Similarly, a 970 Kb inversion polymorphism on human chromosome 17q21.31 is predicted to have inverted at least three times independently in the orangutan, human and chimpanzee lineages [36,85].…”
Section: Origin Of Sdsmentioning
confidence: 99%
“…Another putative case of inversion recurrence, that of the pericentric inversions PTR XVI in chimpanzee and GGO XVI in gorilla has been disproven as the breakpoints are located at non-identical positions and thus must have occurred independently in the two lineages (Goidts et al 2004). So far, the only convincing case of a recurrent inversion is that of the relatively small (~40 kb) FLNA-EMD inversion in eutherians (Cáceres et al 2007). This inversion is the result of non-allelic homologous recombination between a conserved pair of inverted duplications on the X chromosome.…”
Section: Phylogeny Of the Martensis Clustermentioning
confidence: 95%